HAMBATAN UTAMA TRANSFORMASI DIGITAL DALAM PELAYANAN PUBLIK - Purwanto, Purwanto (AKTUAL, 2024)
Digital transformation in local government has a number of benefits for the efficiency of public services. However, implementing digital transformation presents a number of important obstacles. This research aims to identify important obstacles that are priorities for implementation strategies. The research uses a mixed methods approach with a sequential exploratory design. In this research, a qualitative approach was used through case studies to identify several important obstacles. Qualitative analysis through the Analytical Hierarchy Process (AHP) to identify obstacles that are strategic priorities. Data was obtained through interviews with 20 practitioners and academics. The study results found several important obstacles, namely: data integration, regulations/policies between institutions, infrastructure quality, apparatus competency, data security, and citizen literacy. The results of the AHP analysis found that data integration, regulations/policies between institutions, and ICT infrastructure were the main priority obstacles in implementing digital transformation in the case study. The next priority obstacles are apparatus competency, data security and digital literacy.